Dual targeting PD-L1 and 4-1BB to overcome dendritic cell-mediated lenalidomide resistance in follicular lymphoma - Zhong Zheng; Jian-Biao Wang; Rui Sun; Nan Wang; Xiang-Qin Weng; Tian-Yuan Xu; Di Fu; Yan Feng; Peng-Peng Xu; Shu Cheng; Li Wang; Yan Zhao; et al. (Signal Transduction and Targeted Therapy)
Abstract Immunomodulatory agent lenalidomide is effective in treating follicular lymphoma (FL). We conducted the first trial of immunotherapy rituximab plus lenalidomide in newly diagnosed FL in China (NCT03715309). One-hundred and fifteen patients were enrolled and treated with rituximab 375 mg/m2 intravenously on day 0 and lenalidomide 25 mg orally on day 1–10 for 6 cycles of induction treatment, as well as lenalidomide for 6 cycles and rituximab for 8 cycles of maintenance treatment. We found that inferior progression-free survival of the patients was significantly associated with elevated serum β2m and lymph node >6 cm, linking to decreased lymphoma cell autophagy and dendritic cell infiltration within the tumor microenvironment. PU.1 transcriptionally downregulated PD-L1 (Programmed death ligand 1) expression and upregulated 4-1BBL (4-1BB ligand) expression, increased lymphoma cell autophagy and dendritic cell maturation via PD-1/PD-L1 and 4-1BB/4-1BBL interaction. In vitro in co-culture system and in vivo in murine xenograft model, knockdown of PU.1 induced lenalidomide resistance, but sensitized FL cells to bi-specific PD-L1/4-1BB antibody or combined treatment of PD-L1 inhibitor and 4-1BB agonist. Collectively, PU.1 is essential in immunomodulatory effect of FL through PD-1/PD-L1- and 4-1BB/4-1BBL-mediated microenvironmental modulation. Dual targeting PD-L1 and 4-1BB could be an alternative immunotherapeutic strategy in the chemo-free era of FL treatment.